Dual Function Inhibitors of Relevance to Chronic Obstructive Pulmonary Disease - Dou, Dengfeng (2010)
The general strategy and rationale underlying the design of COPD therapeutics that possess protease inhibitory activity and are also capable of releasing a species that attenuates inflammation by inhibiting caspase-1, are described. The synthesis and in vitro biochemical evaluation of a dual function molecule that sequentially inhibits HNE and caspase-1 in a time-dependent manner is reported.